HUMAN BEING DALAM DISKURSUS EKSISTENSIALISME BARAT DAN ISLAM: KOMPARASI PEMIKIRAN JEAN-PAUL SARTRE, GABRIEL MARCEL, MULLA SADRA DAN MUHAMMAD IQBAL - Abdul Najib, Safaat Ariful Hudda, (IAIN Kediri, 2021)
Human nature is a material object of the many developing sciences. This article will focuses on the discussion of human being in terms of existentialism which will be compared between western philosophy and Islamic philosophy. As a limitation, this paper will only discuss Jean-Paul Sartre and Gabriel Marcel from the west tradition and Mulla Sadra and Muhammad Iqbal from the Islamic tradition. This selection is based on thecloseness of their thoughts so that comparisons can be made that are anthropocentric because other philosophers, especially in Islamic tradition, prioritized theological views. This paper finds out that the west and Islam tought tradition, human philosophy has different perspectives and thus has very different ideas. Western philosophy tends to depart from the view of humans as humans themselves or in other words their existence as humans. Meanwhile, Islamic philosophy talks more about human being starting from the view of their relationship with God, although in its development there was a shift towards anthropocentrism. However, the thoughts of the four figures above intersect on the aspect of human being in relation to others. The results of the discussion in this paper shows that it is understood that the western version of philosophical thinking about the relationship between humans and other people emphasizes the rationality and emotional aspects rather than the spiritualprophetic aspects as found in Islamic existentialism.Keywords: Human Being, West-Islam, Rational-Emotional, Spiritual-Profeti